Liquidity Risk and Islamic Bank Performance: A Panel Data Analysis of Banks in MENA and South Asia with a Focus on Morocco - ACHCHAB, Aya (Revue du contrôle, de la comptabilité et de l’audit, 2026)
This study examines the impact of liquidity risk on the performance of Islamic banks in the MENA and South Asian regions, with a particular focus on Moroccan participatory banks. The analysis is based on a panel of 53 banks over the period 2019–2024 and employs econometric models, including pooled OLS, fixed effects, and random effects, with the Hausman test used to select the appropriate specification. The findings indicate that liquidity risk, measured by the loan-to-deposit ratio, has a negative and statistically significant effect on bank profitability. In contrast, bank size positively influences performance, while the liquid assets ratio does not show a significant effect. Beyond these results, the study provides a comparative analysis across regions and highlights the role of institutional context in shaping the relationship between liquidity risk and bank performance. In particular, Moroccan participatory banks exhibit higher exposure to liquidity constraints compared to more mature Islamic banking systems. These findings underline the importance of strengthening liquidity risk management and developing Sharia-compliant financial instruments, especially in emerging banking systems. The study contributes to the literature by providing new comparative evidence on the role of institutional context in Islamic banking performance.